On the effect of the nature of counterions on the self-assembly of polyoxyethylene alkyl ether carboxylic acids. Issue 30 (14th July 2020) - Crivello, Chiara; Lazzara, Giuseppe; Chiappisi, Leonardo
Abstract : In this contribution, we investigate the effect of the type of counterion on the properties of dilute solutions of polyoxyethylene alkyl ether carboxylic acids. Abstract : In this contribution, we investigate the effect of the type of counterion on the properties of dilute solutions of polyoxyethylene alkyl ether carboxylic acids. Two different surfactants, presenting an oleic acid alkyl chain and on-average five and nine ethylene oxide units, and terminated by a weakly anionic carboxymethyl group were studied. The surfactants were gradually ionized with sodium hydroxide, arginine, and choline hydroxide. The solutions properties were probed by light scattering, electrophoretic mobility, density and sound velocity measurements, as well as by small-angle neutron scattering. To our initial surprise, no specific effect arising from the nature of the counterion could be determined. We ascribe this phenomenon to the fact that the presence of the ethylene oxide units markedly dilutes the surfactant head group charge density, reducing counterion condensation and subsequent counterion specific effects.